2015
DOI: 10.2298/vsp141004041n
|View full text |Cite
|
Sign up to set email alerts
|

Cervical poorly differentiated adenocarcinoma with dominant choriocarcinomatous pattern: A case report

Abstract: The early and proper diagnosis of nonmetastatic choriocarcinoma of nongestational origine in coexistence with cervical carcinoma is curable and can have good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Serum value of human chorionic gonadotropin is the most relevant parameter in diagnosis of GTN. It depends on secretion of syncytiotrophoblast which is a hormone active component of trophoblast, and most important marker in monitoring the effect of the treatment and outcome of the disease 4 . In placental site trophoblastic tumor (PSTT), serum levels of chorionic gonadotropin do not have the same significance as they do in other malignant GTN, and they may be negative, making this analysis unuseful.…”
Section: Introductionmentioning
confidence: 99%
“…Serum value of human chorionic gonadotropin is the most relevant parameter in diagnosis of GTN. It depends on secretion of syncytiotrophoblast which is a hormone active component of trophoblast, and most important marker in monitoring the effect of the treatment and outcome of the disease 4 . In placental site trophoblastic tumor (PSTT), serum levels of chorionic gonadotropin do not have the same significance as they do in other malignant GTN, and they may be negative, making this analysis unuseful.…”
Section: Introductionmentioning
confidence: 99%
“…A term ETT was proposed in 1994 for the first time when it was thought that this kind of tumor occurred as a consequence of administering chemotherapy in the patients with choriocarcinoma, i.e., that chemotherapy influenced the tumor growth by mechanism of drug induced cell changes. In 1998 study by Shih and Kurman 1 , it was shown that ЕТТ became an independent entity because it has for some specific histological and immunohistochemical features which make it different from placental site tumor and choriocarcinoma [1][2][3] . ЕТТ origins from intermediate trophoblast and it can overlap with squamous cell carcinoma as per differential diagnosis considering its common localization in the lower uterine segment or cervix when some cases of ETT were noted in oviducts and ligamenta lata 4,5 .…”
Section: Introductionmentioning
confidence: 99%